Feminism and Gender Justice in Pesantren Life: A Case Study at Pondok Pesantren Al-Ikhlas Tambakberas Jombang - Maulidina, Fitrotul; Mubarok, Mohammad Anas; Hamidah, Tutik; Rofiq, Aunur (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
A study on gender justice in pesantren is very important, given the persistent stigma that pesantren are patriarchal institutions that limit women’s roles. In fact, when examined more deeply, pesantren hold great potential in realizing equality values that align with Islamic teachings. This article aims to reveal the implementation of gender justice values at Pondok Pesantren Al-Ikhlas Tambakberas Jombang through educational patterns, daily practices, and the role-modeling of the pesantren caretakers. This research employs a qualitative descriptive method with observation, interviews, and questionnaires distributed to 40 male and female students and pesantren administrators. The findings show that principles of gender justice have been applied at Pondok Pesantren Al-Ikhlas through equitable task distribution, active involvement of female students in pesantren activities, and the exemplary role of KH. Hasyim Yusuf demonstrates engagement in domestic and productive activities regardless of gender. All students stated that the implementation of gender justice has had a positive impact, both in shaping critical thinking and in increasing fair participation among students. This study suggests that feminism can be internalized within the pesantren environment without departing from Islamic values and local wisdom.